The Great Gatsby The Complete 1925 Text with Introduction and Afterword by Richard Smoley - Fitzgerald, F. Scott; Smoley, Richard (New York G&D Media, 2021)
Long regarded as one of the greatest American novels of the twentieth century, this beautiful edition of The Great Gatsby which includes an Introducion and Afterword by Richard Smoley, is the original text which expresses many of the central themes of the American myth: romance, love, the quest for wealth and status, loneliness, and corruption.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books